Extending Instrumental Sea‐Level Records Using Coral Microatolls, an Example From Southeast Asia. Issue 4 (11th February 2022) - Majewski, J. M.; Meltzner, A. J.; Switzer, A. D.; Shaw, T. A.; Li, T.; Bradley, S.; Walker, J. S.; Kopp, R. E.; Samanta, D.; Natawidjaja, D. H.; Suwargadi, B. W.; Horton, B. P.
Abstract: The small number of reliable long‐term (i.e., >50 yrs) tide gauges in tropical locations is a major source of uncertainty in modern sea‐level change. Coral microatolls record relative sea‐level (RSL) change over their lifetimes and have the potential to extend the instrumental record. Here, we examined a 20th and 21st century RSL record from two living coral microatolls from Mapur Island, Indonesia, which produced 16 sea‐level index points. We validated and combined the living coral microatoll data with tide gauge data to show RSL at Mapur Island was 0.0 ± 1.6 mm/yr (2σ) from 1915 to 1990 and 1.0 ± 2.1 mm/yr (2σ) from 1990 to 2019. Through the addition of microatoll RSL data we extended the record of modern sea‐level change by over 50 years and reduced its uncertainty by ∼50%. Plain Language Summary: Long instrumental sea‐level records from tide‐gauges are required to understand regional sea‐level variability, but in most tropical regions tide‐gauge records only began in the latter half of the 20th century. Therefore, there is considerable uncertainty in the regional sea‐level projections in tropical regions, which are necessary for effective coastal risk management. Coral microatolls can extend the duration of tide‐gauge records and provide completely new sea‐level records because their growth patterns reveal important information about sea level during the coral's lifetime. In this study, we examined sea‐level records from living coral microatolls from Mapur Island, Indonesia. We validated the coral microatoll technique to reconstruct sea level with data from the nearby Tanjong Pagar tide gauge in Singapore. The combined coral microatoll and tide gauge data showed sea level change of 0.0 ± 1.6 mm/yr (2σ) from 1915 to 1990 and 1.0 ± 2.1 mm/yr (2σ) from 1990 to 2019. Coral microatolls can extend sea level records for other tropical regions where tide gauges have only recently been installed and provide a new data source in locations where tide gauges have not and might not be installed. Key Points: Validating the coral microatoll technique to reconstruct relative sea level Producing 16 new sea‐level index points from two microatolls between 1915 and 2012 Extending the record of modern sea‐level change by over 50 years and reducing its uncertainty by ∼50%